Assessment of agrochemicals effect on soil and groundwater of Chanchaga irrigation scheme in Minna, North Central Nigeria - Adeoye, Peter Aderemi; Che Man, Hasfalina; Bello, Abdulahi Mohammed (Penerbit UTM Press, 2015)
A study was conducted to assess the effects of long term usage of agrochemicals on soil and groundwater of Chanchaga Irrigation Scheme. Soil and groundwater samples were collected from the scheme for the period of sixteen months and were analysed for NO3, PO4, Cl, K using UV Spectrophotometer and flame photometer and for some heavy metals, Mn, Zn and Cr using Atomic Absorption Spectrophotometer (AAS). The data were subjected to regression and correlation analysis and Analysis of Variance (ANOVA). The results show excessive presence of NO3, PO4, Mn, Zn and Cr in both the soil and water samples. It was observed statistically that all the chemical parameters (NO3, PO4, Mn, Zn and Cr) were significantly different at p=0.05 in both groundwater and soil of Chanchaga Irrigation Scheme. The concentration of Nitrates and Phosphates ranged between 48.45 - 51.63 mg/l and 0.39 - 0.78 mg/l respectively in the water. This could be associated with the used of agrochemicals and fertilizer that are Nitrogen and Phosphorus based by the farmers. Zinc concentration ranged between 0.18-1.84 mg/l in the groundwater. On the average the concentration of manganese and chromium detected differ from one point of collection to the other. However, the concentration ranged between 0.22-0.53 mg/l with the highest concentration of 0.53 mg/l in points 2 and 3 where intensive agricultural practice is being carried out. Chromium concentration ranged between 0.18 0.29 mg/l. The chemical residues in the control site for Nitrate, Phosphate, Manganese, Zinc and Chromium were 48.45 mg/l, 0.39 mg/l, 0.21 mg/l, 0.18 mg/l and 0.04 mg/l respectively which were within the permissible limit. A safe depth of 8m was established statistically for future shallow wells that will guarantee potable water on the irrigation scheme. It is recommended that, to forestall further accumulation of these chemical residues in both soil and shallow groundwater of Chanchaga irrigation scheme, relevant regulatory Government agencies should enforce standard Good Agricultural Practice whereby the farmers are compelled to adhere strictly to existing standard for agrochemical and fertilizer application rate. Also future shallow wells to be constructed on the irrigation scheme must be up to 8 m in depth to guarantee nitrate and chloride free water.